Electricity Connections and Firm Performance in 183 Countries - Geginat, Carolin; Ramalho, Rita (World Bank, Washington, DC, 2015)
This paper presents new data on electricity connections for businesses in 183 economies. The data cover information on procedures, time, and cost that a small or medium size business with a moderate electricity need has to invest to obtain a new electricity connection. The study finds significant variation in the time and cost to obtain such an electricity connection across countries. In low-income countries, for instance, it takes on average nearly twice as long as in high-income countries to connect a new customer to electricity, while the cost associated with a comparable connection is 70 times higher. The study finds that the poor performance of distribution utilities in low-income countries cannot only be explained by differences in income levels. The overall level of bureaucracy appears to be another important factor. The study also finds the data to be correlated with existing measures of the effectiveness of the electricity sector, suggesting that the hurdles related to obtaining an electricity connection mirror other problems in the sector, such as the quality of electricity supply and the incidence of bribe payments. Finally, the study finds that electricity connections affect firm performance. Simpler and less costly electricity connection processes are associated with better firm performance, in particular in industries with high electricity needs, such as manufacturing motor vehicles.